Early Childhood Adversity and Its Associations with Anxiety, Depression, and Distress in Women with Breast Cancer - McFarland, Daniel C (Psychosomatics, 2015)
INTRODUCTION: Certain vulnerability factors have been found to place patients at risk for depression and anxiety, especially within the context of medical illness. Early childhood adversity (ECA) primes adults to become more vulnerable to depression by enhancing their reactivity to stress; this relationship is not adequately described in patients with breast cancer. METHODS: Breast cancer patients (Stage 0-IV) were assessed for ECA (i.e., the Risky Families Questionnaire [RFQ]-subscales include Abuse/Neglect/Chaotic Home Environment), distress (i.e., Distress Thermometer and Problem List [DT&PL]), anxiety (Hospital Anxiety and Depression Scale-Anxiety [HADS-A]), depression (Hospital Anxiety and Depression Scale-Depression [HADS-D]), meeting standardized cut-off thresholds for distress (DT&PL ≥4 or ≥7)/anxiety (HADS-A ≥8)/depression (HADS-D ≥8), and demographic factors. RESULTS: One hundred twenty-five participants completed the study (78% response rate). ECA was associated with depression (p<.001), anxiety (p=.001), and distress (p=.006) and with meeting cut-off threshold criteria for distress (p=.024), anxiety (p=.048), and depression (p=.001). On Multivariate analysis, only depression (p=.04) and emotional issues (i.e, component of DT&PL)(p=.001) were associated with ECA. Neglect, but not Abuse and Chaotic Home Environment, was associated with depression (β=.442, p<.001), anxiety (β=.342, p=.002), and self-identified problems with family (β−.288, p=.022), emotion (β=.345, p=.004), and physical issues (β=.408, p<.001). CONCLUSION: ECA and neglect are associated with multiple psychological symptoms but most specifically depression in the setting of breast cancer. ECA contributes to psychological burden as a vulnerability factor. ECA may help to explain individual patient trajectories and influence the provision of patient centered care for psychological symptoms in patients with breast cancer.